Processes of uniform pseudo-random search of global extremum at current stage of computer technology development - Smirnova S. Y. (Innovative technologies in science and education, 2016)
the article deals withpseudo-occasional numbers generator value impact on result obtaining in the algorithm of random optimization. Much attention is given to insolvency of the standard pseudorandom number generator Microsoft Office in case of the solution of some random optimization task classes; the authors also offer a variant of solution for revealed problem.
Keywords: оптимизация; целевая функция; экстремум функции; optimization; вихрь Мерсенна; гладкая функция; метод Монте-Карло; нелинейное программирование; непрерывная функция; случайный поиск; функция Розенброка; Mersenne twister; smooth function; Monte-Carlo method; nonlinear programming; continuous function; stochastic optimization; Rozenbrock function; objective functions; extremum